Identification and quantitative assessment of motor complications in Parkinson’s disease using the Parkinson’s KinetiGraph™ - Qu, Yan; Zhang, Tingting; Duo, Yunyan; Chen, Liling; Li, Xiaohong (Frontiers in Aging Neuroscience, 2023)
With disease progression and dopamine drug application, some people with Parkinson's disease (PwPD) may develop motor complications such as motor fluctuations and dyskinesia. Early identification and assessment of motor complications are crucial guidelines for optimizing treatment and improving motor function. Scales completed by physicians and disease diaries completed by PwPD are useful, but are limited by physician subjectivity and PwPD compliance, and sometimes are even unreliable. More importantly, it is not possible to perform a continuous and remote assessment. There is a necessity to develop an accurate, objective, and remotely recordable tool to evaluate motor complications in PwPD. The Parkinson's KinetiGraph TM (PKG), the first wearable device approved by FDA for PD recording, has shown obvious advantages over traditional scales. Our research aims to investigate the feasibility of PKG in identifying and assessing motor complications including motor fluctuations and dyskinesia in PwPD, as well as the concordance with the clinical scale assessment. The PKG has a good correlation with clinical scales and high sensitivity and specificity for the identification and diagnostic screening of motor fluctuations and dyskinesia. Therefore, we consider that application in the clinical practice of the PKG can provide clinically meaningful data to aid clinical decision-making, thereby benefiting PwPD. I believe you will enjoy reviewing this work. We look forward to improving our article with your feedback.